Observaciones acerca de un origen transpresivo de la cordillera oriental (1999)
In this paper we consider characteristic relay patterns of marginal folds at both borders of the Eastern Cordillera and confront them with a regional compilation of fault-slip data and a preliminary evaluation of joint sets. Complementary deformation patterns of right-stepped fold pairs along NW-trending borders and left stepped structural relays along a N-S trending deformation front comply to a transpressional deformation with a constrictional strain direction of about 300°. Fault/slickenside  pairs pertain mostly to strike-slip deformations and their populations define, to a first approximation,  pseudoconjugate sets, whose compression or extension directions are emphasised further by reverse or normal fault pairs.  In the Santander Massif the compression directions are oriented both perpendicularly to the NNE striking Bucaramanga fault and to N-S trending,  faulted sedimentary inlayers of the Massif's internal parts. To the W of the Bucaramanga fault, and affecting most of the Bogota segment, the striated faults record a consistent clockwise departure from the perpendicular to the structural trend, reflecting probably a late incremental strain.  In contrast, joints evidence a pre-folding origin and document shortening directions, which support the constrictional bearing derived from the regional analysis. With this initial constellation of a homogeneous far stress field, the model of a simple transpression applies for the folding of the Bogotá segment. In the Santander Massif, this simple transpression is likely to be partitioned into a strike-slip deformation along the Bucaramanga fault at its western border fault and a homogeneous pure shear in the remaining massif. This first appreciation may, however, be modified, considering the presence of a preferred simple shear along sinistral fault planes, which occupy the position of Riedel shears with respect to the Bucaramanga fault, so that some strike-slip deformation may be distributed across the whole  massif.